POTENCIAL USE OF LOCAL WISEDOM OF SASAK (WARIGE) AS SEASONAL RAINCAST IN LOMBOK - Ismail Yasin; Mahrup Mahrup; Fahrudin Fahrudin (Jurnal Cakrawala Ilmiah, 2023)
Climate anomaly has pronounced impact on agriculture in Lombok. Occurence of drought results in crop failure. Up to date our knowledge about the cause of climate anomaly has still vey limited. Better understanding on that matter may contribute better water management and cropping strategy. The aim of this study was to examine the skill of seasonal climate forecast based on Sasak local native knowlledge (warige) which was validated with real time planting practised by farmers in different types of climate in Lombok. The output of this study is expected to be used as additional climate information for integrated crop calendar in Lombok. This study applied descriptive methods with survey technique. Data collected included Luni-solar calendar from 1950 to 2012, monthly rainfall data of 1950 to 2012 from four types of climate in Lombok. Five year daily rainfall in selected areas. To obtain moonphase at overhead sun from 1950 to 2012 it was used Kalender Jawa obtained from http:// www.kalendarjawa.com. Ten points of filed crop observation was established in each tipe of climate (C3); D3 and D4. C3 belongs to technical irrigation, D3 belongs to semi-technical irrigation and and D4 belongs to rainfed adn embung irrigation. All farmers involved in this study were also questioned whether they understand and apply warige in their seasonal crop planning. Results of this studyshowed that SCF based on Sasak local native knowledge had good skill in forecasting wetness and dryness of dry season. The different in amount of rainfall in dry and wet years is fairly significant, but usually wet year rainfall did not differ to moderate years’, neither moderate years’ to dry years’. Nevertheless warige was able to predict distribution of rainfall within month during the dry season. Thus we can predict wether it will enough rainfall for several in coming months